“Reinventing emancipation in the 21st century: the pedagogical practices of social movements” - Motta, S.; Esteves, A. (Interface: A journal for and about social movements, 2014)
Marxist, decolonial, post-colonial, feminist, anti-racist, queer, post-structuralist and autonomist/anarchist critical traditions with differing foci, demonstrate the exclusions and violences at the heart of the emergence and reproduction of capitalism. They foreground how capitalism/modernity is built upon alienations and separations embedded within a world view of individualism, maximization of material gain and processes of subjectification. The worldview or cosmology of capitalism is one based on an instrumental and indifferent relationship to nature, denial of ‘other’ worldviews and devaluing of the emotional and embodied. This is manifested in relationships of power-over, hierarchy and competition in the subjective and social realms and (re)produced through a spatial logic of separation, division and dispossession. Crucially, as feminists have demonstrated these alienated subjectivities and social relationships are also gendered. Emotionality is a feminised construct associated with the irrational, the unruly and the shameful - something to be controlled to avoid disruption to the normal and rational social and physic order. Alienation thus becomes embedded in our bodies, impoverishing our bodily relationships with each other and ourselves, and distorting our emotions resulting in toxic blockages and repressions. Yet as Jamie Heckert (2013) describes ‘to realise that the intertwined hierarchical oppositions of hetero/homo, man/woman, whiteness/color, mind/body, rational/emotional, civilized/savage, social/natural and more are all imaginary is perhaps a crucial step in letting go of them. How might we learn to cross the divide that does not really exist except in our embodied minds?’ And it is here where analytic and political attention to the pedagogical becomes crucial. Underlying and enabling the reproduction of such alienated and alienating ways of inhabiting, knowing and creating the world are a politics of knowledge which, as many of our contributors demonstrate is deeply monological, authoritarian and violent. This involves a conception of the world reflective of the particular interests of dominant groups, becoming ‘incorporated into everyday life as if it were an expression of it, and to act as an actual and active guiding force, giving direction to how people act and react’.